Identification of the key proteins associated with different hair types in sheep and goats - Zhang, Chongyan; Qin, Qing; Liu, Zhichen; Xu, Xiaolong; Lan, Mingxi; Xie, Yuchun; Wang, Zhixin; Li, Jinquan; Liu, Zhihong (Frontiers in Genetics, 2022)
Animal-derived fiber has the characteristics of being light, soft, strong, elastic and a good thermal insulator, and it is widely used in many industries and traditional products, so it plays an important role in the economy of some countries. Variations in phenotypes of wool fibers among different species and breeds are important for industry. We found that the mean fiber diameter of cashmere was significantly smaller than that of sheep wool (p < 0.01), and sheep wool was significantly smaller than goat wool (p < 0.01). Compared with traditional proteomics technology, we analyzed cashmere, guard hair, and wool by Laber-free proteomics technology and detected 159, 204, and 70 proteins, respectively. Through the sequential windowed acquisition of all theoretical fragmentations (SWATH), 41 and 54 differentially expressed proteins were successfully detected in the cashmere vs. wool group and guard hair vs. wool group. Protein‒protein interaction network analysis of differentially expressed proteins revealed many strong interactions related to KRT85, KRTAP15-1 and KRTAP3-1. The final analysis showed that the proportion of KRT85, KRTAP15-1 and KRTAP3-1 might be the key to the difference in fiber diameter and could be used as a potential molecular marker for distinguishing different fiber types.